Evaluation of Chronic Liver Disease: Does Ultrasound Scoring Criteria Help?. (10th September 2013) - Afzal, Shaista; Masroor, Imrana; Beg, Madiha
Abstract : Noninvasive approaches for assessment of liver histology include routine laboratory tests and radiological evaluation. The purpose of our study was to determine the utility of a simplified scoring system based on routinely evaluated ultrasound features for the evaluation of chronic liver disease and correlate it with the histological findings. For this cross-sectional analytical study the data was collected prospectively by nonprobability purposive sampling technique. The ultrasound variables/parameters and their assigned scoring system that was a modified version adopted from published literature were evaluated. Sensitivity, specificity, positive and negative predictive values of the liver morphological score and combined score of liver morphology and sizes was determined using stage and grade as reference standard. Our results show a high sensitivity and PPV of liver morphological sonographic evaluation for the staging and grading of CLD respectively thus supporting it as a screening diagnostic strategy. Of the three liver morphology variables, specificity of liver surface evaluation was highest for the stage of fibrosis and grade of inflammation. The simplified ultrasound scoring system evaluated in our study is clinically relevant and reproducible for differentiating patients with CLD with mild or no fibrosis from moderate to severe fibrosis.